Come to the library - Holden, Pam. (Birkenhead, Auckland, N.Z. : Red Rocket Readers, an imprint of Flying Start Books Ltd., 2006)
Simple text describes what you can learn in a library.
"Emergent level, non-fiction set A"--Back cover.
1.8
Preschool
Preschool
Keywords: Readers (Primary); Vocabulary -- Juvenile literature; Reading; Vocabulary; Reading; Vocabulary; Readers (Elementary)